Pedagogical experiences from the SENA-CEET methodology - Gómez Rodríguez, José Luis
As a stimulus for the appropriation of good pedagogical practices, based on the experiences of the instructors with apprentices in the different technical areas, the Center for Electricity, Electronics and Telecommunications organized a discussion with four of the twenty-seven instructors who obtained outstanding evaluation (> 4.5 / 5.0 ) in the last evaluation. Following are aspects related to the role of the instructor, details of the event, the protagonists and the questions that the pedagogical team prepared for them, as well as relevant findings and the proposal of a decalogue for the SENA instructor.